Spatial distribution and geochemical characterization of Icelandic mantle end-members - Sunna Harðardóttir 1991- (2020)
Supplementary data is provided in the linked Excel file Radiogenic isotopic ratios and major element contents in Icelandic volcanics are used to evaluate mantle end-member compositions and their spatial distribution in the Icelandic mantle. A database, entitled the Icelandic Volcanics Isotopic Database (IVID), which includes previously reported 87Sr/86Sr, εNd, εHf, 206Pb/204Pb, 207Pb/204Pb, 208Pb/204Pb, 187Os/188Os, 3He/4He, δ18O and U-Th decay series isotopic ratios measured in Icelandic volcanics, was compiled. Major and trace element contents were also included in the IVID. Isotopic ratios were evaluated, and filtered based on improvements in analytical methods, major element chemistry and other sample characteristics. The filtered database was used to map the radiogenic isotopic composition of Icelandic volcanics by creating isoscapes superimposed on a map of Iceland. Spatial analyses demonstrate that volcanics from the off-rift volcanic zones tend to be geochemically more enriched (higher 87Sr/86Sr and 206Pb/204Pb and lower 143Nd/144Nd and 176Hf/177Hf) in their radiogenic isotopic composition than volcanics from the axial rift zones. High-MgO (≥ 8 wt%) volcanics demonstrate correlations between major elements and isotopic ratios, where the more enriched off-rift volcanic zone volcanics are characterized by higher TiO2, Na2O, K2O, FeOT and K2O/TiO2 and lower, SiO2, CaO and Na2O/TiO2. PRIMELT calculations demonstrate that the enriched off-rift volcanic zone volcanics are generally produced at lower temperatures and by lower melt fractions, consistent with preferential sampling of geochemically enriched and fertile “blobs” at lower degrees of melting; more geochemically depleted volcanics on the axial rift zones show higher degrees of melting at higher temperatures, consistent with dilution of enriched blob melts by melts of more depleted and refractory mantle. Isotopically distinct components have been identified in the Icelandic mantle and 3He/4He is used to estimate which components are part of the ...